Evaluation of Free Fatty Acid Content in Rice Bran Oil Used in Commercial Poultry Feeding in India - R, Kavitha; A, Natarajan; R. P. Senthil Kumar; M.Siva; S.R, Janani (Indian Journal of Animal Nutrition, 2024)
An investigation was made to evaluate free fatty acid content (FFA) of rice bran oil (RBO) regularly used in commercial poultry feeding. A total of 1815 rice bran oil samples used in commercial poultry feeding, submitted between 2012 and 2021 by feed manufacturers, farmers from various parts of India, were analyzed for FFA content at Animal Feed Analytical and Quality Assurance Laboratory, Veterinary College and Research Institute, Namakkal, Tamil Nadu. RBO samples submitted for FFA analysis was initially less in numbers between 2012 and 2018 (63 in 2013 to 178 in 2018) but it increased thereafter in 2019 (298), 2020 (322) and 2021 (291) which showed increased awareness to test the quality of RBO through analysis of the free fatty acid content and increased use of oil as a source of energy in poultry. Among the samples analyzed the FFA was found to be in the range between 0.50 and 38.44 per cent with a mean value of 6.99 ± 0.08. From the investigation, around 11.0 % of RBO samples tested in the last 10 years had more than 10% FFA which, when only by routine analysis can be avoided from being used.